MongoDB administration - Mohite, Jayant (Packt, 2019)
"MongoDB is a very popular open source cross-platform document-oriented database program. This comprehensive tutorial is your one-stop guide to all the aspects of MongoDB administration. You will start with jumping into the configuration, indexing and aggregation aspects of MongoDB. You'll also see how you can optimize your query performance. Later, we'll explore the core administration tasks such as deployment, replication, sharding, and application. This course will equip you with all the skills you need to manage a highly efficient database."--Resource description page